1990
DOI: 10.1002/pola.1990.080280212
|View full text |Cite
|
Sign up to set email alerts
|

High molecular weight aromatic polymers by nickel coupling of aryl polychlorides

Abstract: This paper describes a totally new method for the formation of high molecular weight aromatic polymers. High molecular weight polyarylethersulfones are produced by nickel catalyzed coupling of aryl dichloride monomers. Metallic zinc is used to drive the polymerization reaction which takes place under relatively mild conditions in the presence of triphenylphosphine and a dipolar aprotic solvent. The versatility of the reaction is demonstrated, as well as the ability to provide a variety of high temperature poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
2

Year Published

1991
1991
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(66 citation statements)
references
References 25 publications
1
63
0
2
Order By: Relevance
“…4-Chloro-1-naphthaleneboronic acid (3) was synthesized from 4-chloro-1-bromonScheme 2. Ni( 0 ) -catalyzed polymerization of 2,5-aphthalene ( 2 ) by lithiation with n-butyl lithium and bis (4-chloro-1-naphthyl) biphenyl ( 6 ) . subsequent reaction with trimethyl borate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4-Chloro-1-naphthaleneboronic acid (3) was synthesized from 4-chloro-1-bromonScheme 2. Ni( 0 ) -catalyzed polymerization of 2,5-aphthalene ( 2 ) by lithiation with n-butyl lithium and bis (4-chloro-1-naphthyl) biphenyl ( 6 ) . subsequent reaction with trimethyl borate.…”
Section: Resultsmentioning
confidence: 99%
“…The resulting brown suspension was added to a CuCl solution (7.548 g, 76.25 mmol in 40 Scheme 1. Synthesis of 2,5-bis( 4-chloro-1-naphthy1)biphenyl (6) mL of concentrated HC1) which had been prepared and stored in an ice/water bath. Since the mixture became thick and the magnetic stirring was not possible, the mixture was stirred by a glass rod occasionally.…”
Section: Synthesis Of Monomermentioning
confidence: 99%
See 1 more Smart Citation
“…23, No. 4,1991 various substituents have also been prepared. The limitations for the aryl chlorides were described, for example, nitro groups completely inhibited the reaction, and acidic substituents, such as phenolic hydroxyl and carboxylic acids, caused reduction to arene.…”
Section: Model Reactionmentioning
confidence: 99%
“…Recently, we showed that nickel-catalyzed coupling polymerization of aryl dichlorides containing ether~ketone structures is a very useful method for the synthesis of aromatic poly( ether ketone )s. 3 In order to expand the preparative utility of this method, it was applied to the synthesis of aromatic poly(ether sulfones)s. Quite recently, the synthesis of aromatic poly(ether sulfone)s by nickelcatalyzed coupling of aryl dichlorides has been reported. 4 This article describes a successful synthesis of aromatic poly(ether sulfone)s by nickelcatalyzed coupling of aromatic dichlorides containing ether sulfone structures.…”
mentioning
confidence: 99%